Efektivitas Implementasi Program Yess dalam Erspektif Principal Agent di Kabupaten Pasuruan - Muhammad Rikzul Fikri; Aminullah Aminullah (Journal of Management and Bussines (JOMB), 2024)
The aim of the research is to determine the effectiveness of implementing the Yess Program from the Principal Agent's perspective in Pasuruan Regency. In this case, the principal-agent condition can be a factor that influences the implementation of the Yess program. Where agency problems often occur, such as Information Asymmetry, Adverse Selection, and Moral Hazard. The research results show that the implementation of the Yess program in Pasuruan Regency is carried out by the DIT (District Implementation Team) and is responsible to the Coordinator. In conclusion, agency problems can be handled well by the Coordinator and DIT (District Implementation Team) in Pasuruan Regency. So that the implementation of the Yess program can be carried out effectively. Keywords: Effectiveness, Principal Agent, Yess Program